2011
DOI: 10.1007/s11524-011-9621-2
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Urban Form, Social Environment, and Depression

Abstract: We examined whether neighborhood urban form, along with the social environment, was associated with depressive symptoms in a sample of Miami residents. Using a validated measure of depressive symptoms, we found that living in neighborhoods with higher housing density was associated with fewer symptoms. A larger acreage of green spaces was also linked to fewer depressive symptoms but did not reach significance in the full model. Our results suggest that how residents use the environment matters. Living in neigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
87
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(107 citation statements)
references
References 40 publications
(59 reference statements)
7
87
2
Order By: Relevance
“…Research findings suggest that positive neighborhood environments are related to positive determinants of mental health, such as, parks for walking, while negative neighborhood environments are related to negative determinants of mental health, such as, stressors from chronic exposure to car traffic and noises [20]. Also, studies have shown that living in a neighborhood with disproportionate high burden of autocommuters relative to land area was associated with more depressive symptoms than living in areas with lower autocommuter density [37].…”
Section: The Built Environment and Mental Healthmentioning
confidence: 95%
See 3 more Smart Citations
“…Research findings suggest that positive neighborhood environments are related to positive determinants of mental health, such as, parks for walking, while negative neighborhood environments are related to negative determinants of mental health, such as, stressors from chronic exposure to car traffic and noises [20]. Also, studies have shown that living in a neighborhood with disproportionate high burden of autocommuters relative to land area was associated with more depressive symptoms than living in areas with lower autocommuter density [37].…”
Section: The Built Environment and Mental Healthmentioning
confidence: 95%
“…Meanwhile, the disabling effects of behavioral health disorders can worsen chronic physical health conditions and disrupt a person's ability to comply with treatment regimen, carry out daily activity and work, to mention just a few reasons. There are few studies that have examined the impact of social environments on mental health [20], and fewer studies focused on the built environment's impact on mental health [21][22][23]. Emerging research has established the association between neighborhood environments and mental health, particularly depression [22][23][24][25].…”
Section: The Built Environment and Mental Healthmentioning
confidence: 99%
See 2 more Smart Citations
“…Peschardt and Stigsdotter's (2013) work addressing the restorative effect of 'green spaces' upon stressed users provides support for the perceived salutary effect of a natural environment; whilst their work does not focus specifically upon noise, 'absence of noise' is included within the perceived benefits of a 'serene' green space. Rocha et al (2012) and Miles et al (2012) echo the importance of environmental noise to the likely prevalence of common mental health disorders (CMD); Rocha et al (2012) suggest that efforts to reduce the prevalence of CMD should be targeted at improving living environments. Honold et al (2012) echo the importance of noise as a potential stressing factor in an individual's living environment.…”
Section: Noise Stress and Health Care Systemsmentioning
confidence: 99%